Formation of personal qualities of students in inclusive education - Nurseit, А.Т.; Bciscnbckova, G.B.; Danek, Jan (Karagandy University of the name of acad. E.A. Buketov, 2023)
This article discusses the ways and methods of formation of personal qualities of students in inclusive education. The problem of rethinking, reassessing and affirming new values is now more acute than ever. Teachers are tasked with training not only well-educated, but also highly moral people. At the present stage, the school is the public institution that is designed to influence the formation of a system of values in the souls and minds of citizens of the country, the development of the qualities of the child's personality. Personality formation is the process of development and formation of personality under the influence of external influences of upbringing, training, social environment; purposeful development of personality or any of its sides, qualities under the influence of education and training; the process of becoming a person as a subject and object of social relations. Personal qualities are psychological characteristics of a person, manifested through relationships to others and to himself in human behavior and activity. Note the qualities of the student's personality, which are indicated in the documents of education: Guarantees of the right of children to receive education are enshrined in the Constitution of the Republic of Kazakhstan, The Laws of the Republic of Kazakhstan "On the rights of the child in the Republic of Kazakhstan", "On Education", "On social and medical-pedagogical correctional support for children with disabilities", "On social protection of disabled people in the Republic of Kazakhstan", "On special social services".
Keywords: inclusive education; formation; personal quality; limited health opportunities; special education; knowledge; disability; social environment